My eyes are up here: the comedy of Amy Schumer and the carnivalesque - Windholz, Benjamin P. (Kansas State University. K-State Libraries, 2014)
Through the lens of Bakhtin's carnivalesque, I analyze stand-up comic Amy Schumer's Comedy Central special Mostly Sex Stuff. Her use of sexual material juxtaposes the material upper and lower stratums and subverts the social structure of gender roles through chaos and humor, specifically through the use of the grotesque body as a site in which to grapple with abstract concepts like sexism. Schumer's attractive looks contrast her archetypical unruly woman stage persona and attack the hegemony of sexism in American culture while also challenging perceptions of race and class. Schumer's carnivalesque satire eviscerates the image of the classical body, with its roots in oppression and power disparity, offering instead a body that is constantly in process which unifies people through its relation to the cosmic. I show how Schumer's use of these ideas transforms her otherwise dirty comedy into subtle social criticism, generating feminist commentary in the male dominated field of stand-up comedy.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Citation: Windholz, B. (2014) My eyes are up here: the comedy of Amy Schumer and the carnivalesque. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Carnivalesque; Women; Rhetoric; Stand-up comedy; Gender; Submersion